ANALISIS HUBUNGAN INTERDEPENDENSI ANTARA KEPUTUSAN INVESTASI, HUTANG DAN DIVIDEN PERUSAHAAN- PERUSAHAAN PROPERTI GO-PUBLIC DI BURSA EFEK JAKARTA - Wahyuningsih Wahyuningsih (Universitas Trisakti, 2001)
The main objective of this study is to examine the interrelationships among investment, debt and dividend decisions as a major decision in financial management. These decisions should be made integratively as the companies could increase their value for their stakeholders. The study is focused on property companies listed in BEJ. Using SURapproach, this study shows that the relationship between investment and dividend decisions is negative andbidirectional, and the relationship between invest- ment and debt decisions is positive and bidirectional, and no relationship is found between dividend and debt decisions. Thus, the study results suggest that the inter- relationship among the three decisions are not really integratively made yet.